2015
DOI: 10.1017/s1047951115001626
|View full text |Cite
|
Sign up to set email alerts
|

A 16-year-old with ST elevation myocardial infarction: case report and review of the literature

Abstract: Chest pain in young adults presents a unique diagnostic challenge, placing young patients at an increased risk to be misdiagnosed, as this patient population typically does not demonstrate the traditional risk factors associated with cardiovascular disease. This study details the case of a 16-year-old male who presented with new-onset chest pain and ST elevation on electrocardiogram. His history was unremarkable for known cardiac risk factors, but laboratory evaluation demonstrated markedly elevated troponins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
1
9
0
1
Order By: Relevance
“…Excessive intake of energy drinks have previously been reported to be associated with various cardiovascular impairments, including cardiac arrhythmias, prolonged QT interval and myocardial ischemia and infarction [14]. In the case of myocardial ischemia, evidence is still limited to a few case reports [6,[15][16][17]. A small prospective study demonstrated the detrimental effects of energy drinks on platelet and endothelial function most notable an acute increase of platelet aggregation and a decrease of endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive intake of energy drinks have previously been reported to be associated with various cardiovascular impairments, including cardiac arrhythmias, prolonged QT interval and myocardial ischemia and infarction [14]. In the case of myocardial ischemia, evidence is still limited to a few case reports [6,[15][16][17]. A small prospective study demonstrated the detrimental effects of energy drinks on platelet and endothelial function most notable an acute increase of platelet aggregation and a decrease of endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…Остання, що виникла внаслідок поєднаної дії двох токсичних чинників (текіли та марихуани), маскувала клінічні прояви гострого коронарного синдрому, який трансформувався в гострий ІМ. У подібних випадках існує ризик неправильної діагностики, оскільки зазвичай відсутні поширені чинники ризику, пов'язані із серцево-судинними захворюваннями [14].…”
Section: обговоренняunclassified
“…We herein discuss the case of a previously healthy 35-year-old man who presented with ST-segment elevation myocardial infarction and was found to have 100% occlusive CAD. This is generally an uncommon event when compared to the elderly, with few cases reported globally [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%